Leader follower tracking and simulation for two aerial robots - Goh, Si Min (Nanyang Technological University, 2024)
Leader Follower is a formation control method used in the world for multi robot system. There are many benefits that a leader follower aerial robots can bring us such as help us in the search and rescue in disaster scenario, agriculture, security problem and more. Although the development of aerial robot has make significant progress over the years but they are still faced with many challenges and problems. Problems such as communication reliability, collision, scalability and cost. The focus of this project is to model, assess, design and simulate leader-follower tracking strategies for two Aerial robots, as well as to compare different controller of the leader-follower tracking strategies for two Aerial robot by using MATLAB for simulation purposes.